Emociones en el proceso de aprendizaje en los niños de inicial II del “Club de Conquistadores” en la ciudad de Quito. - Simbaña Molina, Paulina Margoth (2024)
This research project covers the impact of emotions on the learning of Intial II, with a focus on the World Organization of the Pathfinder Club during the 2023-2024 period. The study emphasizes the importance of emotional well-being in the cognitive, social, and emotional development of preschool-aged children. Talking about Latinamerica, cultural and socioeconomic diversity poses challenges in integrating effective pedagogical strategies that address the emotional needs of children. The research focuses on Ecuador, where many institutions lack training and resources to implement emotional education practices. The study highlights the relevance of emotional education as part of children's integra development, influencing their autonomy and ability to interact with others. The general objective is to analyze the impact of emotions on the learning of children in Initial II of the "Pathfinder Club" in the city of Quito, understanding how emotional experiences affect motivation, attention, memory, and active participation in educational activities. The main findings indicate that positive emotions, such as joy and interest, increase children's motivation and participation. In contrast, negative emotions such as anxiety and frustration reduce attention and concentration. Additionally, emotional connection to educational content improves information retention, and proper emotional management fosters more active and constructive participation. The methodology included a detailed analysis of how emotions affect children's cognitive and socio-emotional foundations. Theories by Piaget, Vygotsky, and Goleman were applied to understand this interconnection. The research highlights the need for educational strategies that manage emotions to improve the educational environment and promote the comprehensive development of children. The conclusions emphasize that emotions play a crucial role in the learning and overall development of Initial II children. It is essential to provide continuous teacher training and adequate resources for effective emotional education programs. Promoting educational policies that integrate emotional education and fostering ongoing research on the intersection between emotions and learning is fundamental.